Analisis Quality Control terhadap Risiko Kerusakan Produk dan Kendali Kualitas Produk Bersih: Studi Kasus pada UMKM Keripik Pisang Az-Zahra Desa Sindangsari Purwakarta - Puspasari, Dewi (https://jurnal.binamandiri.ac.id/, 2024)
Product quality is a reflection of the product's production process. Production process stages that comply with standards will produce products of good quality. The more products produced, the more profits a business will gain. Conversely, if the number of products produced is not of good quality, the product can be categorized as a failed product (product defect). This research aims to analyze quality control in a case study at Az-Zahra MSMEs using the quality control method with the help of POM-QM for Windows software to measure the risk of product failure so that Az-Zahra MSMEs can implement quality control on clean products. Based on the results of p-charts calculations reviewing problems in the production of UMKM Az-Zahra Banana Chips for the period January to December 2023, it can be seen that the limit for failed products turns out that the number of failed products in September 2023 exceeds the upper control limit. The condition of the filling or filling process in each period is running normally. Furthermore, the net weight of Az-Zahra banana chip products is still within control limits.